(untitled) (مجلة الهندسة, 2008)
This paper presents a study of the geometrically non-linear vibrations of clamped circular plates with variable thickness by taking the effect of large amplitude motion. The maximum thickness is considered to be at the plate center and it is taken to be twice the value of thickness at the edge. The problem is solved by the numerical iteration procedure to obtain the results of vibration amplitudes up to twice the maximum plate thickness. The results are presented for the first two modes of vibration. The obtained results indicate that increasing the ratio of thickness has the effect of increasing the nonlinear frequency and modify the corresponding mode shape.